1987
DOI: 10.1159/000184164
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Gram-Positive Peritonitis with Two Intraperitoneal Doses of Vancomycin in Continuous Ambulatory Peritoneal Dialysis Patients

Abstract: Eight patients with end-stage renal failure on continuous ambulatory peritoneal dialysis (CAPD), who developed peritonitis, received an intraperitoneal dose of vancomycin (30 mg/kg body weight) with 6 h of peritoneal dwell and then resumed their routine CAPD schedule. Vancomycin concentration in serum, peritoneal dialysate (PD) from an overnight dwell and 1, 2 and 3 h after a new exchange was measured at 48 h (in 5 patients) and 7 days (in 6 patients). Except for an occasional 1-hour peritoneal fluid sample on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In short, we think that the tobramycin and vancomy cin dosages recommended by Bastani et al [1] may be toxic, all the more when both drugs are associated and frequently used. On the other hand, we agree upon the necessity of using two antibiotics right from the start of the treatment in order to rapidly control infection before knowing the responsible germ.…”
Section: Dear Sirmentioning
confidence: 92%
“…In short, we think that the tobramycin and vancomy cin dosages recommended by Bastani et al [1] may be toxic, all the more when both drugs are associated and frequently used. On the other hand, we agree upon the necessity of using two antibiotics right from the start of the treatment in order to rapidly control infection before knowing the responsible germ.…”
Section: Dear Sirmentioning
confidence: 92%
“…This was echoed by Bastini et a1 57 and Boyce et a1 " who, by means of a comparative study involving 51 patients, concluded that vancomycin once weekly for two weeks was as effective and safe as conventional continuous dosing.…”
Section: Epidermidismentioning
confidence: 94%
“…Morse et al, 55 after initial pharmacokinetic studies, recommended a single 30mg/kg dose of vancomycin once weekly for three weeks." This was echoed by Bastini et a1 57 and Boyce et a1 " who, by means of a comparative study involving 51 patients, concluded that vancomycin once weekly for two weeks was as effective and safe as conventional continuous dosing.…”
Section: Antibiotic Administrationmentioning
confidence: 94%
“…Therefore, after i.v. administration of vancomycin to a CAPD patient, serum concentrations may remain elevated for prolonged periods, leading to a dosing interval of about 5 to 7 days in anuric patients (12,13,25). Once-weekly dosing is therefore adequate in such patients for even the most serious deep tissue infections.…”
Section: Vancomycin Pharmacakineticsmentioning
confidence: 99%
“…administration, and a variety of different i.p. vancomycin regimens and doses have been advocated (10)(11)(12)(13)(14)(15)(16)(17)(18). In 1993 the Ad Hoc Committee proposed initial therapy for CAPD peritonitis to include vancomycin 2 grams i.p.…”
mentioning
confidence: 99%